2011
DOI: 10.1016/j.bpj.2011.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Inhibits the Formation of β-Sheet-Rich Oligomers of the Alzheimer's Amyloid-β(16-22) Peptide

Abstract: Alzheimer's disease is associated with the abnormal self-assembly of the amyloid-β (Aβ) peptide into toxic β-rich aggregates. Experimental studies have shown that hydrophobic nanoparticles retard Aβ fibrillation by slowing down the nucleation process; however, the effects of nanoparticles on Aβ oligomeric structures remain elusive. In this study, we investigate the conformations of Aβ(16-22) octamers in the absence and presence of a single-walled carbon nanotube (SWCNT) by performing extensive all-atom replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
246
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(272 citation statements)
references
References 69 publications
21
246
1
1
Order By: Relevance
“…REMD methods are useful to sample a large set of configurations in different potential wells separated by high energy barriers, which otherwise is not possible in a classical MD simulation. Indeed, temperature-based REMD (T-REMD) simulations were used in several studies to accelerate the sampling of peptide-surface interactions Li et al 2011;Oren et al 2010) and of interactions of basic fibroblast growth factor (bFGF), a small protein, with a hydroxyapatite (001) surface (Liao & Zhou, 2014). Liao and Zhou observed that while the protein displaces the surface hydration shell and binds tightly to the surface in the T-REMD simulations (five replicas in the range from 310 K to 2500 K), bFGF did not contact the surface directly in classical MD simulations at 310 K (Liao & Zhou, 2014).…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…REMD methods are useful to sample a large set of configurations in different potential wells separated by high energy barriers, which otherwise is not possible in a classical MD simulation. Indeed, temperature-based REMD (T-REMD) simulations were used in several studies to accelerate the sampling of peptide-surface interactions Li et al 2011;Oren et al 2010) and of interactions of basic fibroblast growth factor (bFGF), a small protein, with a hydroxyapatite (001) surface (Liao & Zhou, 2014). Liao and Zhou observed that while the protein displaces the surface hydration shell and binds tightly to the surface in the T-REMD simulations (five replicas in the range from 310 K to 2500 K), bFGF did not contact the surface directly in classical MD simulations at 310 K (Liao & Zhou, 2014).…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Fullerenes were shown to inhibit fibril formation by binding to the hydrophobic KLVFF sequence [21], while multiwalled carbon nanotubes and graphite were shown to promote their formation [19,64]. However, computer simulations have suggested that SWCNTs can inhibit the formation of amyloid from Aβ peptide fragments 16-22 and 25-35 [65,66], demonstrating that further studies are required to address this issue.…”
Section: Resultsmentioning
confidence: 99%
“…48,49 This primitive defense mechanism employed by cells to aggregate melanin, [37][38][39][40][48][49][50] a strategy employed to build a scaffold for melanin assembly, forming at least a barrier against pathogens or foreign bodies, 48,49 has been recently associated with oxidative damage and inflammation in several different types of cells. 49 We demonstrate the presence of amyloid in lung, liver, and brain of MWCNT-exposed mice.…”
Section: Discussionmentioning
confidence: 99%
“…36 In this context, data concerning the ability of CNTs to induce protein aggregation and amyloid fiber formation are controversial. [37][38][39][40] The NLRP3 inflammasome, associated with immune responses to CNTs, [27][28][29][30]41 activates release of IL-18, 42 a cytokine associated with amyloid plaque formation in Alzheimer's disease, [43][44][45][46] a neurodegenerative disorder characterized by amyloid accumulation. For these reasons, we investigated the ability of CNTs to induce amyloid production and deposition in vivo, an innate defense mechanism present in most eukaryotic phyla ranging from fungi and invertebrates [47][48][49] to humans.…”
Section: Introductionmentioning
confidence: 99%